Mathematical functional for thermal distribution calculating during the electron-beam welding process. Issue 5 (April 2020) - Kurashkin, S O; Seregin, Yu N; Tynchenko, V S; Petrenko, V E; Murygin, A V
Abstract: In this paper, we researched the influence of the electron beam defocus on the quality of the weld. The carried-out research was based on the theory of the thermal field using mathematical models developed by the authors. As a criterion of optimality, the previously developed thermal functional was used. We obtained criteria that can be used to simulate processes in electron beam welding, and to obtain more accurate modes, which is necessary to bind to power equipment. The obtained results of the criteria can be used for electron beam welding of various materials and different thicknesses.